Energy efficiency improvement of medical electric tools and devices; MATEC Web of Conferences; Vol. 19 : The 2nd International Youth Forum "Smart Grids", Tomsk, Russia, October 6-10, 2014 - Meshkov A. S.; Susdorf V. I.; Dementiev Yu. N. Yuriy Nikolaevich; Kaftasyev D. A. (2014, 2014)
Title screen